Key word : (Larousse, 2014)
Chambers English key word dictionary has been specially written so that it can be used by even the most inexperienced learner. Written in clear, simple English, this dictionary is an ideal first monolingual dictionary for elementary and lower intermediate students. Users will find many of the features that appear in Chambers more advanced ETL dictionaries, but presented in a hidhly simplifified form